ملامح مشروح النقد التطبيقي عند عماد الدين خليل من خلال كتابه في النقد التطبيقي - بن عمر, الجيلاني; صحراوي, حداء; زكري, عبد المالك (University of Eloued جامعة الوادي, 2024)
نلخص بحثنا الذي هو تحت عنوان (ملامح مشروع النقد التطبيقي عند عماد الدين خليل من خلال كتابه في النقد التطبيقي) في جانبين هما: - الجانب النظري: تعرضنا إلى تعريف النقد التطبيقي و تطوره عند القدامى و المحدثين, ثم بينا الملكات و الوسائل التي يجب أن يتسلح بها الناقد التطبيقي, ثم تعرضنا لأهم المناهج المتبعة في ذلك. - الجانب التطبيقي: و هو الأهم فقد ركزنا على نقد النقد لديوان ثلاثية الغيب و الشهادة, و ديوان المتخصص و الرصد المبكر. و أما النثر فقد اقتصرنا على قصة منصور لم يمت و هي حلقة من سلسلة أطفال الحجارة. Our research, entitled "Characteristics of Imad Eddine Khalil's project of applied criticism through his book on applied criticism", is divided into two parts, the first theoretical and the second practical. - In the theoretical section, we first define applied criticism and its development in ancient and modern authors. Next, we set out the qualities and means that each critical author must have in order to succeed in his or her applied criticism. Finally, to close this section, we discussed the most widely used approaches to this task. - As for the practical part, we concentrated mainly on the criticism of two collections. The first is "The Trilogy of the Invisible and Testimony" and the second is "The Specialist's Collection and Early Observation". As far as the prose is concerned, we've limited ourselves to the story "Mansour n'est pas mort", which is an episode in the "Children of the Stones" series.
نقد حديث ومعاصر
Keywords: نقد النقد - النقد التطبيقي - مواجهة النص - تطور النقد التطبيقي - ملامح النقد التطبيقي - الناقد التطبيقي - وسائل الناقد - الوعي بالالتزام - القدس - أطفال الحجارة - الغيب - الشهادة.; The criticisme of criticism - Applied criticism - Facing the text - The development of applied criticism - Features of applied criticism - Applied critic - Critic means - Commitment awareness - alquds - Children of stones - The unseen - the Testimony